Implementasi Program Zakat Produktif: Ternak Desa Sejahtera (TDS) dalam Meningkatkan Kesejahteraan Mustahik di LAZNAS Nurul Hayat Madiun - Rifa'i, Khabib Musthofa; Anhar, Fibrianis Puspita (Nidhomiya: Research Journal of Islamic Philanthropy and Disaster, 2025)
Productive zakat is one of the key instruments in empowering the economic potential of the ummah, particularly for mustahik with the capacity to become self-sufficient. LAZNAS Nurul Hayat Madiun developed the “Ternak Desa Sejahtera” (TDS) program as a form of zakat distribution by providing livestock assistance to mustahik. However, in practice, the program has encountered several technical and resource- related challenges that may hinder its intended outcomes. This study aims to examine the implementation of the TDS program, including the supporting and inhibiting factors, as well as its impact on mustahik welfare. The research applies a descriptive qualitative method, with data collected through interviews, observations, and documentation involving program managers and beneficiary mustahik.The findings reveal that the TDS program is managed systematically through planning, beneficiary selection, mentoring, and evaluation stages. Success factors include active participation by mustahik and continuous assistance from the institution, while the main obstacles involve technical issues such as feed supply and weather conditions. The program has had a positive impact on mustahik’s income, economic independence, and confidence in running livestock-based businesses.